1987
DOI: 10.1103/physrevd.35.282
|View full text |Cite
|
Sign up to set email alerts
|

Fritzsch-Stech model in SO(10)

Abstract: The combined Fritzsch-Stech model for quarks is consistent with our present knowledge of quark masses and mixing angles. A possible way to extend it to leptons-by using an SOilO) framework-has been suggested by Bottino, Kim, Nishiura, and Sze. We investigate this model further and find some new features. It is first noted that the allowed quark masses are somewhat sensitive to the experimental uncertainties in the input parameters. This is carefully analyzed and we find that the original Stech Ansatz for the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Finally we discuss the case of (V O) 2 P 2 O 7 -a spin chain compound whose magnetic properties have given rise to controversial interpretations. This compound has been initially considered as an ideal realization of a twoleg antiferromagnetic Heisenberg spin ladder [43]. Subsequently, however, it has been shown that the susceptibility data on polycristalline material could be well fitted by either a ladder or an alternating chain model [44].…”
Section: Discussion Of Experimental Datamentioning
confidence: 99%
“…Finally we discuss the case of (V O) 2 P 2 O 7 -a spin chain compound whose magnetic properties have given rise to controversial interpretations. This compound has been initially considered as an ideal realization of a twoleg antiferromagnetic Heisenberg spin ladder [43]. Subsequently, however, it has been shown that the susceptibility data on polycristalline material could be well fitted by either a ladder or an alternating chain model [44].…”
Section: Discussion Of Experimental Datamentioning
confidence: 99%
“…Vanadyl pyrophosphate (VO) 2 P 2 O 7 is a gapped antiferromagnet with spin 1/2 and had long been known as a good model compound of a two-leg antiferromagnetic Heisenberg spin ladder. [1][2][3] Recently, dispersion of the magnetic excitations was measured using the inelastic neutron-scattering technique and is found to be inconsistent with a simple ladder model. 4 Although an alternating Heisenberg antiferromagnetic chain is proposed as an alternative magnetic model of (VO) 2 P 2 O 7 , the suggested direction of the chain is not readily known from the crystal structure and the excitation spectrum is not fully compatible with a simple alternating spin chain.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of several families of new materials, [1][2][3] such as (VO) 2 P 2 O 7 , Sr n−1 Cu n O 2n−1 (n = 2, 3, . .…”
Section: Introductionmentioning
confidence: 99%